Flood Routing Numerical Model Linked-up by Rivers and Flood Detention Basins - Yu Fan, Pengtao Wang, Yanqing Li, Daming Li (Forest Chemicals Review)
This paper presents a combined flood routing numerical model of one-dimension and two-dimension. The authors use the Finite Volume Method (FVM) in this model. The river-pattern grids and ground-pattern grids connect each other at multi-point and multi-passage in this model. Multi-point means many nodal points with relationship to each other, and multi-passage refers to the flow cross-sections at different dam break. Blocking buildings are modeled as broad crest weir flow. The model is well adapted to the complex conditions of rivers and five flood detention basins. The model is applied to Daqinghe detention Areas. The model simulates the flood routing process based on the “August 1996” flood data of Daqinghe detention areas, we verify the water level and discharge in rivers and flood reaching time in detention areas, and the verification results are satisfactory. Then we simulate the flood routing of 100 years return period, thus provides fundamental basis for flood control and disaster alleviation. The results of the study have been used to Daqinghe detention areas in Tianjin, and that gets good effect.